Health Self-Assessment in Students of Pomeranian Medical University in Szczecin - Jasińska, Maria; Żułtak-Bączkowska, Katarzyna; Rotter, Iwona; Dugiel, Grażyna; Szych, Zbigniew; Karakiewicz, Beata (Polish Journal of Public Health, 2010)
Background. The analysis of health self-assessment in students of the Faculty of Health Sciences at the Pomeranian Medical University (PAM) in Szczecin. The students know the principles of healthy life style and are supposed to think of health in terms of life success. Aim. To learn about students’ attitude to promotion of their own health. Material and method. The study involved 217 students of the Faculty of Health Sciences at the Pomeranian Medical University (PAM). Results. A considerable number of students lead unhealthy life style, which does not change with job seniority. Conclusions. It is necessary to emphasize the importance of health promotion and positive attitude towards patients and ourselves in the process of education.